OUR TEACHERS ARE THE LIGHT OF KNOWLEDGE AND PROFESSION: history of Departments of Surgery of the Tashkent Medical Academy - Khudaiberganova, N.Sh.; Bobabekov, A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
World famous surgeons such as P.P. Sitkovsky, Orlov I.I., Voyno-Yasenetsky V.F., Borovsky P.F. The school organized by them for the training of medical personnel under the program of the medical faculties of the University began to study from 08/15/1919. Professors and teachers who arrived on a special medical train from Moscow in May 1920 met with the organizers and employees of the already functioning medical school. In the structure of the medical faculty of the Turkestan State University, 3 departments of surgery were organized. This is the Department of General Surgery with a course of urology - Professor Pereshivkin N.S., Department of Hospital Surgery - Professor P.F. Borovsky and the Department of Faculty Surgery - Professor P.P. Sitkovsky. It was they who made a great contribution to the organization and functioning of these departments.